Reminiscence Therapy For Cognitive Improvement and Mood Recovery in Dementia Patients - Fery Agusman Motuho Mendrofa; Umi Hani; Ni Nyoman Maryaningtyas Adinatha; Dicky Dwispataru (Universitas STRADA Indonesia, 2021)
Dementia is a degenerative condition that affects the cognitive function of the elderly. Symptoms of dementia include memory disorders, difficulty finding words, and disturbances in thought processes, personality, or emotional changes so that dementia can cause the elderly to be easily lost or lost. Purpose: This study aimed to determine the effectiveness of reminiscence therapy on cognitive and mood improvement in elderly people with dementia. This study was a quasi-experimental approach. This study used one group pre and post-test design. The study was conducted in October 2019 with a total sampling technique including 30 respondents who met the inclusion and exclusion criteria. The results show that the cognitive function improved after reminiscence therapy (mean of SPMSQ decreased from 5.7 to 3.13). The mood also improved after reminiscence (the mean of mood increased from 57.6 to 77.16). Reminiscence therapy is effective for cognitive and mood enhancement in dementia.